Effects of herbs and spice on health status of tilapia (Oreochromis mossambicus) challenged with Streptococcus iniae - Aydın, Seyit; Gültepe, Nejdet; Yılmaz, Sevdan; Bilen, Soner; Güroy, Derya (University of Veterinary and Pharmaceutical Sciences, 2014)
Effects of different herbal extracts on the growth and immune defense of fish were researched in the last decade. The aim of this study was to determine the dietary effects of thyme (Thymus vulgaris), rosemary (Rosmarinus officinalis) and fenugreek (Trigonella foenum graecum) as a feed additive on haematology, innate immune response, and disease resistance of tilapia (Oreochromis mossambicus). In total 228 healthy fish tilapia were divided into four groups (57 fish in one group) and fed diets supplemented with thyme, rosemary and fenugreek at levels of 1%, respectively; fish in the control group were fed diet without any spices. Fish were fed ad libitum three times a day for 45 days. All fish of the experimental groups significantly (P < 0.05) enhanced phagocytic activity, haematocrit, white blood cell, red blood cell, neutrophil and monocyte counts in blood. Significant (P < 0.05) increase of plasma myeloperoxidase and lysozyme activity was found in fish receiving a feed supplemented with fenugreek after 30 days. Respiratory burst activity was non-significantly (P > 0.05) changed during the whole experiment. After 45 days of feeding, fish were injected intraperitoneally with 100 μl of Streptococcus iniae (8 × 108 colony forming unit). The cumulative mortality was 22%, 27% and 31% in fish receiving diets supplemented with 1% thyme, rosemary and fenugreek, respectively, compared to 61% mortality in the control group. The results indicate that all three supplements used improved the haematological status, non-specific immune response and disease resistance of tilapia against S. iniae; this is the first similar study.
Keywords: 2. Zero hunger; 14. Life underwater; 3. Good health